Effect of Exercise and Zoledronic Acid on Lipid Profile and Bone Remodeling in Ovariectomized Rats - Khashaba, M.B.B.CH. MD. PhD, Ahmed Sayed; Al Batati, Fawaz Salem; BDS, MSc, Abdulrhman Al Saffan (International Journal of Innovative Research in Medical Science, 2018)
Exercise (EXE) and amino-bisphosphonates (BP) are both considered as useful strategies in the prevention of post-menopausal bone loss. Exercise reduces lipid levels, and BP may induce increase in high-density lipoprotein cholesterol (HDL-C). We hypothesized that combined effects of BP and exercise would produce a better improvement of lipid profile. (Dolléans, 2010) Non pharmacological prevention of osteoporosis fracture by physical activity and particularly regular exercises (EXE) characterized by impact or loading is currently recommended.The effect of regular exercise on the Lipid profile has been developed in a lot of studies It has been recently demonstrated that increasing steps walked may have beneficial effects on serum lipids and thus may decrease the cardio vascular disease risks. Conversely, physical activity, and more specifically mechanical stress, has been shown to induce an osteogenic effect mediated by osteocytes and osteoblasts. (Howe, 2011) Sixty 6-month old Wistar female rats were maintained under the standard environmental conditions of light and temperature, (12 h light: 12 h dark photoperiod, at 24 ±2 oC) with free access to water. They were divided into 3 groups according to methods of induction